Striking elevation in incidence and prevalence of inflammatory bowel disease in a province of western Hungary between 1977-2001 - Lakatos, Laszlo (World J Gastroenterol, 2004)
AIM: An investigation into inflammatory bowel disease and colorectal cancer in Veszprem Province was conducted from 1977 to 2001. METHODS: Both hospital and outpatient records were collected and reviewed comprehensively. The majority of patients were followed up regularly. RESULTS: The population of the province was decreased from 386000 to 376000 during the period. Five hundred sixty new cases of ulcerative colitis (UC), 212 of Crohn’s disease (CD), and 40 of indeterminate colitis (IC) were diagnosed. The incidence rates increased from 1.66 to 11.01 cases per 100000 persons for UC, from 0.41 to 4.68 for CD and from 0.26 to 0.74 for IC. The prevalence rate at the end of 2001 was 142.6 for UC and 52.9 cases per 100000 persons for CD. The peak onset age in UC patients was between 30 and 40 years, in CD between 20 and 30 years. A family history of IBD was present in 3.4 % in UC and 9.9 % in CD patients. Smoking increased the risk for CD (OR = 1.94) while it decreased the risk for UC (OR = 0.25). Twelve colorectal carcinomas were observed in this cohort, the cumulative colorectal cancer risk after 10 years in UC was 2%, after 20 years 8.8%, after 30 years 13.3%. CONCLUSION: The incidence and prevalence rates of IBD have increased steadily in Veszprem Province, now equivalent to that in Western European countries. Rapid increase in incidence rates supports a probable role for environmental factors. The rate of colorectal cancers in IBD is similar to that observed in Western countries.